Parents’ perceptions and experiences of the decision making process when choosing secondary school placement for children with statements of special educational needs: an interpretative phenomenological analysis - Booth, Laura (2017)
Government legislation has promoted parental rights when choosing educational provision for children with statements of Special Educational Needs (SEN) over the past two decades (Department for Education, [DfE], 1994, 2014) and acknowledges the importance of this decision to parents (DfE, 2011). A review of relevant literature suggested that implementation of such reforms may not be straight forward for parents due to the political and economic dynamics within the wider education system (Bajwa-Patel and Devecchi, 2014; Norwich, 2014). A review of research literature on parents’ perceptions and experiences of the decision making process suggested that parents are significantly influenced by information available and their interactions with others, including the education providers and local authorities, through a process of decision making which they described as a ‘struggle’ and a ‘fight’ (Jessen, 2012; Bajwa-Patel and Devecchi, 2014; Lalvani, 2012). Therefore, the current study aimed to develop a deeper understanding of parents’ experiences and perceptions of the decision making process when choosing secondary school for their child with a statement for SEN within a local authority in England. Six semi-structured interviews with eight parents, who had recently been through the process, were analysed using Interpretative Phenomenological Analysis as the methodological approach. Master themes emerged, which highlighted the influence of emotional reactions when being shown round by staff in prospective secondary schools and the inconsistency of communication with professionals experienced by different parents. Implications are discussed for supporting parents in feeling that they are able to make more informed decisions and in achieving a more consistent approach across professionals to support a more positive experience for parents.